13th Computational Fluid Dynamics Conference 1997
DOI: 10.2514/6.1997-2097
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive least-squares method for the compressible Euler equations

Abstract: SUMMARYAn adaptive least-squares finite element method is used to solve the compressible Euler equations in two dimensions. Since the method is naturally diffusive, no explicit artificial viscosity is added to the formulation. The inherent artificial viscosity, however, is usually large and hence does not allow sharp resolution of discontinuities unless extremely fine grids are used. To remedy this, while retaining the advantages of the least-squares method, a moving-node grid adaptation technique is used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…More recently, impressive results using anisotropic elements have been reported by Habashi et al 12,13,14,15,16,17 With their approach, all grid adaptions are local operations, as opposed to global remeshings. Highly-stretched elements are obtained, achieved by equating the interpolation error along each edge, again using a spring analogy minimization.…”
Section: Introductionmentioning
confidence: 85%
“…More recently, impressive results using anisotropic elements have been reported by Habashi et al 12,13,14,15,16,17 With their approach, all grid adaptions are local operations, as opposed to global remeshings. Highly-stretched elements are obtained, achieved by equating the interpolation error along each edge, again using a spring analogy minimization.…”
Section: Introductionmentioning
confidence: 85%
“…In Gnoffo's work, structured grids are replaced by tension springs, and the spring stiffness is defined as a function of the gradient of certain flow property so that more nodes could be "pulled" to the regions with higher gradient. Subsequently, Nakahashi and Deiwert [1985;1987a;1987b] introduced torsion springs into Gnoffo's spring model to increase the orthogonality of the structured grids, and Ait-Ali-Yahia et al [1996] and Taghaddosi et al [1997] combined the vertex spring analogy method with an edge-based error estimator and developed a directionally adaptive finite element method for quadrilateral grids. From these work, it was found that the vertex spring analogy method is very effective for both 2D and 3D structured grids.…”
Section: Introductionmentioning
confidence: 99%
“…Also in LSFEM, non-self-adjoint equation systems, such as the ones that govern fluid dynamics, result in symmetric positive-definite global system matrices, which can be solved efficiently by iterative solvers. In literature it is possible to find many uses of LSFEM for the solution of compressible flows (Fletcher, 1979;Jiang and Carey, 1990;Taghaddosi et al, 1999;Moussaoui, 2003;Reddy et al, 2004;Gerritsma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Jiang and Carey (1987) used LSFEM with h-type adaptive 2D, non-conforming quadrilateral meshes. Taghaddosi et al (1999) and Guaily and Megahed (2010) used LSFEM on r-refined quadrilateral meshes. Chang and Chen (2011) coupled LSFEM with a re-triangulation algorithm to perform optimal adaptive solutions of advection-diffusion equation on 2D triangular meshes.…”
Section: Introductionmentioning
confidence: 99%